HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN SIBLING RIVALRY PADA BALITA DI DESA PARAHU KABUPATEN TANGERANG - Octaviani, Linda; Budi, Nanang Prasetyo; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
Parenting style is one of the factors that influence the incidence of sibling rivalry in children aged 3-5 years. As many as 82% of children experience sibling rivalry. The purpose of this study was to study the effect of parenting styles on the incidence of sibling rivalry in children aged 3-5 years in Parahu Village, Sukamulya District, Tangerang Regency. Parahu Village, Sukamulya District, Tangerang Regency. Research method Descriptive correlation cross sectional approach of the population in this study were parents in Parahu Village, Sukamulya District, Tangerang Regency as many as 50 respondents. Sampling technique with total sampling. The instrument used is a google form. The results of the research data analysis used were univariate and bivariate analysis using the chi square test and the Spearman rank correlation, it was found that there was a relationship between parenting patterns and the incidence of sibling rivalry in toddlers, as the results of the statistical test p value 0.000 with r 0.468, which means that there is a significant relationship. have medium. The conclusion of the research results were all respondents based on the results of good parenting as many as 12 people 24.0% and there was a significant relationship between parenting and the incidence of sibling rivalry in toddlers with p value = 0.000 <0.05.